Are standards effective in improving automobile fuel economy? An international panel analysis - Clerides, Sofronis; Zachariadis, Theodoros (My University, 2007)
There is an intense debate over whether fuel economy standards or fuel taxation is the more appropriate policy instrument to raise fuel economy and reduce CO2 emissions of cars. The aim of this paper is to analyze the impact of standards and fuel prices in new car fuel economy with the aid of cross-section time series analysis of data from 18 countries. We employ a dynamic specification of new car fuel consumption as a function of fuel prices, standards and per capita income. Results are used to address policy questions that are currently in the center of discussions worldwide: to what extent the implementation of fuel economy standards has yielded fuel savings; how much fuel prices should rise in order to increase fuel economy without tightening standards; and whether autonomous fuel economy improvements should be expected in the absence of regulations or fiscal policy instruments.
Keywords: CAFE; Fuel tax; Greenhouse gases; Rebound effect; Regulation; Technical progress; JEL classification: Q4